Handbook of stable isotope analytical techniques - Groot, Pier Anne de, 1950- (Elsevier, 2004)
This two volume reference serves as a handbook containing a wealth of information for all isotope chemists working in a wide range of disciplines including anthropology to ecology; drug detection methodology to toxicology; nutrition to food science; and the atmospheric sciences to geochemistry. Complementing the first volume, Volume II includes matters that are not strictly confined to analytical techniques themselves, but relate to analysis of stable isotopes such as the views on the development of mass spectrometers, isotopic scales, standards and references, and directives for setting up a laboratory.